Superheroes, Movies, and the State : How the U.S. Government Shapes Cinematic Universes - Jenkins, Tricia; Secker, Tom (Book collections on Project MUSE., 2021)
"Despite continued warnings of "superhero fatigue," Marvel and DC's current cinematic universes (the MCU and DCEU) have dominated the last two decades of popular culture and continue to obliterate box-office records. Where other scholars have focused solely on superhero films' global popularity, reflections of American imperialism, cultural legacy, or treatment of minority groups, Jenkins and Secker examine these films' production-side relationships with the American Department of Defense (DOD), NASA, the Science and Entertainment Exchange (SEEX), and other government agencies that have aided (or withdrawn from) their creation and promotion. This government-entertainment complex, they argue, uses superhero films as non-traditional propaganda: the state does not directly generate or force the creation of these movies, but instead leverages its unique resources to encourage positive images and messaging. Positive portrayals of the state differ from movie to movie, and military and scientific agencies emphasize different "American values," but their methods are similar and their efforts can coincide. By using documents obtained from government entertainment liaison offices through years of FOIA requests (including script notes, production correspondence, and marketing materials), as well as personal interviews with both producers and government liaisons, Jenkins and Secker illustrate how and why state agencies invest in the production of superhero films, how their support-or lack thereof-influences those films' final narratives, and how both studios' past films and current story arcs offer opportunities to diversify their future productions"--